May the Centrifugal Force be with you

A particle of mass m rotates with a uniform angular speed ω \omega . It is viewed from a frame rotating about the Z-axis with a uniform angular speed ω o \omega_{o} . The centrifugal force on the particle is:

a is the radius.

m ω o 2 a m\omega_{o}^{2}a m ( ω + ω o ) 2 a 4 \frac{m(\omega +\omega_{o})^{2}a}{4} m ω 2 a m\omega^{2}a m ω ω o a m\omega\omega_{o}a

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Arjen Vreugdenhil
Jan 13, 2018

The centrifugal force enters into the picture in a frame that rotates relative to an inertial frame. If the angular speed of the rotating frame is ω 0 \omega_0 , then the centrifugal force on a particle at distance a a from the axis of rotation is F c f = m ω 0 2 r F'_{cf} = \boxed{m\omega_0^2 r} in the outward direction, never mind what the motion of the particle is, or what other forces are acting.


To complete the analysis: From a non-rotating frame, the particle must be subject to a centripetal net force, resulting from an applied force F a p p l i e d = F n e t = m ω 2 r , F_{applied} = F_{net} = -m\omega^2 r, where the negative sign indicates inward direction. When this particle is viewed from the rotating frame, it appears to be traveling with relative angular velocity ω = ω ω 0 \omega' = \omega - \omega_0 . In this frame, we conclude that F n e t = m ( ω ) 2 r = m ( ω ω 0 ) 2 r , F'_{net} = -m(\omega')^2r = -m(\omega - \omega_0)^2 r, but we also know that there is a centrifugal force F c f = m ω 0 2 r F'_{cf} = m\omega_0^2 r , and well as a Coriolis force F c o r = 2 m ω 0 ω r F'_{cor} = 2m\omega_0\omega' r . Therefore the particle must be subject to an applied force F a p p l i e d = F n e t F c f F c o r = m ( ω ) 2 r m ω 0 2 r 2 m ω 0 ω r = m ( ( ω ) 2 + 2 ω 0 ω + ω 0 2 ) r = m ( ω + ω 0 ) 2 r = m ω 2 r . F'_{applied} = F'_{net} - F'_{cf} - F'_{cor} = -m(\omega')^2 r - m\omega_0^2 r - 2m\omega_0\omega' r \\ = -m((\omega')^2 + 2\omega_0\omega' + \omega_0^2)r = -m(\omega' + \omega_0)^2 r = -m\omega^2 r. Therefore in both systems we draw the same conclusion about the applied force that is driving the rotating particle.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...